(untitled) (Voice of Teacher, 2024)
The present research examines Fahrenheit 451 as a critique of censorship and its effects on common people during the time of the Cold War and the McCarthy Era in the United States. Examined through the lens of cultural studies, the practices of censorship on book reading become a state violation of an individual’s agency. Thus, Gay Montag, the main character in the novel and a firefighter in twenty fourth century world, becomes a site of the state’s oppression. As a representative character, Montag is an example of the contemporary American people Bradbury saw in 1950s America. In this context, Montage and his aides’ attempt to memorize books so that they can use their knowledge for future use becomes a beacon of hope in an apocalyptic world rife with state oppression.